PENGELOLAAN SAMPAH DARI BANK SAMPAH DI DESA ADAT CEMENGGAON DENGAN PROGRAM â€œPESAN-PEDEâ€ YANG DIURAIKAN MENJADI â€œPENGELOLAAN SAMPAH MANDIRI PEDESAANâ€ - I Komang Dedi Diana; I Wayan Arissusila (JURNAL SEWAKA BHAKTI, 2021)
Waste management from a waste bank in Cemenggaon Traditional Village with the "PESAN-PEDE" program which is described as "Independent Rural Waste Management". This work program is carried out on Sunday, September 13 2020 at 5.00 - Finish at the Cemenggaon Traditional Village Waste Bank. The service was carried out through a qualitative descriptive approach. This approach is expected to produce descriptive data in order to reveal the causes and processes of occurrence. Community service is carried out in Cemenggaon Traditional Village, Celuk Village, Sukawati District, by carrying out waste bank activities with the â€œPESAN PEDEâ€ program, which is described as 'Independent Rural Waste Management', independent means that management is carried out at sources of waste and rural means that it is carried out by rural / customary communities, especially in handling household organic waste